2009
DOI: 10.3354/meps08307
|View full text |Cite
|
Sign up to set email alerts
|

Character lability in deep-sea bamboo corals (Octocorallia, Isididae, Keratoisidinae)

Abstract: Morphological traits that appear multiple times when mapped onto molecular phylogenies have been associated with character lability. In an ecological context, functional characters, if labile, could confer advantages for adaptation to specific habitats. Bamboo corals are long-lived, deep-sea octocorals characterized by an obvious modularity, which affords diverse branching morphologies in the Keratoisidinae subfamily. We reconstructed molecular phylogenies using 16S (mitochondrial) and ITS2 (nuclear) ribosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Bayer, 1956). However, studies over the last 15 years have shown that in many cases species delimitations and systematics based on these morphological traits keep little to no correspondence with the patterns of genetic diversity and relatedness inferred using mitochondrial and ribosomal DNA sequence markers (Dueñas and Sánchez, 2009;France, 2007;McFadden et al, 2006). A confounding factor when analysing mitochondrial DNA markers is the fact that anthozoans, including octocorals, have slow rates of sequence evolution relative to other metazoans (Hellberg, 2006;Shearer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bayer, 1956). However, studies over the last 15 years have shown that in many cases species delimitations and systematics based on these morphological traits keep little to no correspondence with the patterns of genetic diversity and relatedness inferred using mitochondrial and ribosomal DNA sequence markers (Dueñas and Sánchez, 2009;France, 2007;McFadden et al, 2006). A confounding factor when analysing mitochondrial DNA markers is the fact that anthozoans, including octocorals, have slow rates of sequence evolution relative to other metazoans (Hellberg, 2006;Shearer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As for shallow-water octocorals, deep-water octocorals present significant challenges for taxonomists, with few morphological characters being available for species delimitation (for example, McFadden et al, 2010). In addition, several studies have shown conflicting patterns of morphological and molecular data (France, 2007;Dueñas and Sánchez, 2009;Pante and France, 2010), suggesting that an integrative approach to taxon delimitation must be applied in this group (for example, Schlick-Steiner et al, 2010). Octocorals, as with other anthozoans (for example, scleractinians and sea anemones), are also plagued with remarkably low levels of mitochondrial genome evolution that renders the use of classical barcoding gene regions such as cox1 of limited use (McFadden et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, certain types of deep-sea coral, such as bamboo corals (jointed gorgonian octocorals; family Isididae, order Alcyonacea), can provide archives of ambient and surface water conditions at interannual to decadal resolution [e.g., Noe and Dullo, 2006;Thresher et al, 2009Thresher et al, , 2010LaVigne et al, 2011;Sinclair et al, 2011;Hill et al, 2014;Farmer et al, 2015aFarmer et al, , 2015bSaenger and Watkins, 2016;Thresher et al, 2016]. As bamboo corals grow (~50-180 μm/yr), calcareous internodes and organic nodes are simultaneously precipitated using distinct carbon sources: proteinaceous nodes incorporate particulate organic carbon, whereas high-Mg calcite internodes incorporate ambient dissolved inorganic carbon [Andrews et al, 2005;Roark et al, 2005;Noe and Dullo, 2006;Tracey et al, 2007;Thresher et al, 2009;Hill et al, 2011;Frenkel et al, 2017]. As such, individual bamboo coral specimens have the potential to provide continuous interannual to decadal records of both ambient (intermediate or deep waters) and surface water conditions over several hundred years.…”
Section: Introductionmentioning
confidence: 99%